Unirational differential curves and differential rational parametrizations. (May 2021) - Fu, Lei; Li, Wei
Abstract: In this paper, we study unirational differential curves and the corresponding differential rational parametrizations. We first investigate basic properties of proper differential rational parametrizations for unirational differential curves. Then we show that the implicitization problem of proper linear differential rational parametric equations can be solved by means of differential resultants. Furthermore, for linear differential curves, we give an algorithm to determine whether an implicitly given linear differential curve is unirational, and in the affirmative case, to compute a proper differential rational parametrization for the differential curve.